Self-Assessment Exercises in Emergency Radiology I – Abdominal Trauma. Issue 2 (1st June 2012) - Archer, J; Russell, Rob; Perry, J
Abstract : This is the first of three self-assessment articles which aim to further readers' understanding of diagnostic imaging and its integral role in the management of patients with emergency conditions, through a series of case studies.